La estructura como generadora de espacios arquitectónicos (2006)
The structural system from the antiquity has been part of the process of creation of spaces and it has been reflected in the architectural works as an apparent element of evolution, from the conception of the space like the experience of man, until the representation of its own imagination. This process is studied in such constructions as the airports where the structural elements make part of a language of meanings that at the moment evoke the spaces like symbols of a universe of feelings and perceptions. The utilized structural system does not only achieves alone the function of supporting, but at the same time of containing in each element a code that allows the relationship of the real thing with that imagined, decisive aspect to conceive the spaces like a bond to the world of the fantasy that has shown in the human being like yearnings of its own existence through the time.